Posebnosti starostnika s poudarkom na komunikaciji - Črnčec, Mateja (Obzornik zdravstvene nege, 2001)
The article deals with specific characterists of the elderly in the light of communication as an inherent part of nursing care. The articlr summarizes basics characteristics of old people and different aspects of communication. Effective communication requires good knowledge of old people, considerationn of individual differences and capacity for the establishement of genuine relationships which is one of the basic tasks of a nurse. The aim of a genuinerelationship is creative problem solving and timely responsible reaction to them.
Keywords: komunikacija; medicinske sestre; starostniki